(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
Jakarta, as a global city, must seek a distinctive economic growth model to provide unique experiences for visiting tourists. The relocation of the capital to Nusantara will require Jakarta to prepare a new economic model filled with stability to avoid spillover effects on Jakarta’s economy since it will no longer function as the center of government. The concept of eventonomics is the study of the economic impact of hosting major events, including red-hot industries, MICE (Meetings, Incentives, Conferences, and Exhibitions) events, and multisport events, which can become sources of economic growth packaged within the concept of urban tourism. This can generate foreign exchange as a form of service export and the potential for foreign direct investment that drives economic growth. By replicating Swiftonomics in Singapore, analyzed using the 2016 input-output table and iterated with the RAS Partial Survey to produce the 2023 input-output table, the study examines impacts on output, employment effects, income multipliers, output multipliers, and linkages. The research results show a potential output increase of Rp65.85 trillion and an additional 8.3 million jobs. The sectors with the highest multipliers are wholesale and retail trade; repair of motor vehicles and motorcycles, while the income multiplier is highest in the manufacturing sector, which is labor-intensive.